2015
DOI: 10.1111/agec.12193
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ preferences for fresh broccolis: interactive effects between country of origin and organic labels

Abstract: While international trade in organic products has grown significantly, understanding consumers' preferences for imported organic foods has remained limited. This research examines the impact of country-of-origin labeling on US consumers' choices of organic foods. Results show that consumer valuation of domestically produced organic broccoli was significantly higher than that of imported organic broccoli. Adding information about USDA organic certification standards/rules for imported products mildly increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
71
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 42 publications
13
71
0
4
Order By: Relevance
“…Interest in country of origin of a food is understood to be a preference of consumers for foods produced in their own country [19,20], following either from inferences about food quality and safety, or a belief that locally produced foods are better for the local economy. The ranking of important issues on food labels is not consistent across countries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interest in country of origin of a food is understood to be a preference of consumers for foods produced in their own country [19,20], following either from inferences about food quality and safety, or a belief that locally produced foods are better for the local economy. The ranking of important issues on food labels is not consistent across countries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Certification provides a signal to consumers to eliminate the uncertainty that consumers are facing when purchasing food products [8,16,17]. Consequently, it is considered as a useful instrument to prevent unsafe foods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In developed countries like the US, it is required to provide country-of-origin of food products such as shells, fresh vegetables, and fruits [17]. Loureiro and Umberger (2007) reported that US consumers were prepared to pay an extra of 1.90 dollars per lb.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The key role of consumer demand for the development of the organic market has also given rise to a growing literature (Aschemann-Witzel and Zielke, 2015, Hemmerling et al, 2015, Hughner et al, 2007, Rödiger and Hamm, 2015. Although there are many studies of consumer preferences for COO on the one hand and organic food on the other, research on COO effects in the context of organic food is scarce (Xie et al, 2015). More specifically, there is a lack of research on how consumers evaluate imported organic food products.…”
Section: Introductionmentioning
confidence: 99%